Promoting school readiness through a preschool feeding program: A nutritional nudge to improve at-risk preschooler’s cognitive development in Armenia - Knauer, Heather A.; Balasanyan, Sona; Bakhshinyan, Elmira; Alderman, Harold (International Food Policy Research Institute, 2021)
Many school feeding programs target child hunger, nutritional deficiencies, attendance, and education outcomes but often do not examine their effects on cognitive development. In this cluster-randomized controlled trial, we tested the effects of adding a morning snack to a school lunch program on the fluid intelligence of 951 children ages 4 to 6 years. While there were no significant effects on development overall, the morning snack improved short-term memory (STM) and total score on the Wechsler Preschool and Primary Scale of Intelligence, Fourth Edition (WPPSI-IV) among children from the lowest quartile of household expenditures (STM: 0.35SD, p = 0.020; WPPSI-IV: 0.65SD, p = 0.087), and those whose mothers completed secondary school or less (STM: 0.35SD, p = 0.002; total WPPSI-IV: 0.81SD, p = 0.011). For at risk preschoolers, school snack programs may help meet their developmental needs.